Ionic Self-Assembly of Beryllon ll and BC18 (Benzyldimethylstearyl-ammoniumchlorid) – Synthesis, Structure, and Thin Films - Madsen, Andreas; Willumsen, Anna; Petersen, Mathias (UCPH NanoScience - a student research journal, 2017)
N/A